Genetic resistance to gastrointestinal parasites in artificially infected Horro and Menz Ethiopian sheep breeds - Haile, Aynalem; Tembely, S.; Anindo, D.O.; Rege, J.E.O.; Mukasa-Mugerwa, E.; Yami, A.; Baker, R.L. (Ethiopian Society of Animal Production, 2000)
Genetic resistance to artificially acquired gastrointestinal parasites was studied in 49 Horro and 103 Menz breeds of Ethiopia. The experimental design involved 2 breeds, 2 infection treatments (Infected vs Non infected) and 3 dietary protein treatments using 152 lambs assigned to the 12 treatment combinations, with an average of about 13 animals per cell. Diets were formulated to be isocaloric but with varying protein and/or nitrogen sources. Infection treatment involved repeated infection and drenching up to a third level. In the first two infections, the `infected' group of lambs were exposed to an experimental infection of 1000 L3 (third stage larvae) of Haemonchus contortus given orally three times a week for 3 weeks. On tertiary infection however, mixed infections of Haemonchus contortus, Longistrongylus elongata and Trichostrongylus colubriformis involving a dose rate of 500 L3 was given three times a week for 12 weeks. Faecal egg output was monitored three times a week starting 3 weeks after the first dose. Packed cell volume was monitored weekly up to 3 weeks from the initial dose of larvae and 3 times per week thereafter. Body weight changes were recorded weekly. In naive lambs in the primary infection, the Horro lambs were more resistant than Menz lambs as shown by their significantly lower FEC No differences were observed in PCV during primary infection. In the secondary and tertiary infection periods, while there was no breed difference for FEC, the Menz had a significantly higher PCV than the Horro lambs. At the end of the tertiary infection, all the infected lambs were necropsied (18 Horro and 26 Menz) and worm counts were recorded. Although, there was no significant breed difference in FEC in lambs prior to necropsy, the Menz lambs had significantly lower worm burdens for H. contortus and L. elongata than Horro lambs, but there was no difference between the breeds for T. colubriformis worm burdens. Both the worm count and PCV data suggest that Menz lambs acquire the ability to resist and tolerate endoparasite infections better than the Horro lambs.